Preparation method of high-toughness ultra-fine grain titanium alloy material

The method of large deformation warm rolling and heat treatment in the metastable phase region, combined with optimized chemical composition, enhances titanium alloy strength and toughness, addressing the limitations of existing alloys.

CN119194162APending Publication Date: 2024-12-27SHANGHAI JIAOTONG UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411277330.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-12
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Existing titanium alloys, such as TC4, suffer from low yield strength, tensile strength, and elongation, limiting their application in modern industries despite their advantages in low density, biocompatibility, and corrosion resistance.

Method used

A method combining large deformation warm rolling in the metastable phase region with heat treatment to create an ultrafine lamellar structure and nano-precipitation phase, optimizing chemical composition with elements like Al, V, Fe, B, and Zr, and employing processes like vacuum induction melting and electron beam cooling.

Benefits of technology

The method produces a titanium alloy with yield strength of at least 1200 MPa, tensile strength of 1400 MPa, and elongation of at least 8%, significantly improving mechanical properties while maintaining low production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194162A_ABST
    Figure CN119194162A_ABST
Patent Text Reader

Abstract

The invention relates to a high-strength and high-toughness ultra-fine grain titanium alloy material and a preparation method thereof, and relates to the technical field of titanium alloys, the high-strength and high-toughness ultra-fine grain titanium alloy material comprises the following chemical components in percentage by weight: 3.0 to 6.0 percent of Al, 1.0 to 2.5 percent of V, 0.5 to 2.0 percent of Fe, 0.01 to 0.25 percent of B, 0.05 to 0.15 percent of C, 0.05 to 0.10 percent of N, less than or equal to 0.05 percent of H, 0.01 to 0.02 percent of Zr, 0.01 to 0.02 percent of Y, 0.01 to 0.1 percent of Si and the balance of Ti and inevitable impurities. The preparation method comprises the following steps: 1, vacuum induction melting and electron beam cold bed furnace melting; 2, performing homogenization treatment; 3, hot rolling cogging and large-deformation warm rolling are conducted, specifically, hot rolling cogging and large-deformation warm rolling are conducted on the material subjected to homogenization heat preservation treatment; and 4, structure refining heat treatment. The finally prepared high-toughness ultra-fine grain titanium alloy material has excellent mechanical properties, the yield strength is not lower than 1200 MPa, the tensile strength reaches 1400 MPa, and the total ductility is not lower than 8%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of titanium alloy material processing, and in particular relates to a high-strength and toughness ultrafine-grained titanium alloy material and a preparation method thereof. Background Art

[0002] Titanium alloys have the advantages of low density, good biocompatibility, excellent comprehensive mechanical properties, and good corrosion resistance. They play an important role in aerospace, medical equipment, and many industrial fields. Usually, the microstructure of titanium alloys is composed of an α phase with high strength and hardness and a β phase with good plasticity. By adjusting the content and morphology of the α phase and the β phase, titanium alloys with different properties can be obtained. However, the lower yield strength and tensile strength have become the shortcomings of titanium alloys, limiting the application of titanium alloys. Taking the commonly used TC4 (Ti-6Al-4V) titanium alloy as an example, under conventional heat treatment process, its yield strength is about 800MPa, the tensile strength is less than 1200MPa, and the elongation after fracture is about 10%. Therefore, through reasonable composition adjustment, exploring new manufacturing processes, and preparing low-cost titanium alloys with higher strength and toughness has always been widely concerned by scientific researchers.

[0003] Large deformation warm rolling refinement is an effective way to improve both the strength and toughness of materials. In recent years, the research on the preparation of ultrafine grains or nanocrystalline materials by large deformation warm rolling has received extensive attention from scientific researchers. As a severe plastic deformation process, large deformation rolling can effectively refine the grains and improve the mechanical properties of the material; at the same time, it can improve the internal structure of the material, making it more uniform and dense; the process is relatively simple and low in cost, and can achieve micro-customization of the material texture and organization, thereby improving production efficiency. The warm rolling process can effectively improve the processing properties of metals, improve plasticity and deformation capacity, and avoid high-temperature oxidation and cold rolling hardening problems; in addition, warm rolling also reduces energy consumption and production costs, thereby improving economic benefits.

[0004] Patent document CN 115971249 B provides a method for preparing ultra-thin TC4 titanium alloy sheet, including hot rolling blanking, hot rolling double heat, quenching, hot rolling triple heat, double sheet stacking, steel plate cladding rolling, cold rolling and step annealing. The overall deformation rate of titanium alloy sheet is more than 99%, and various thickness blanks can be formed into ultra-thin sheets with a thickness as low as 0.4mm. Through combined hot rolling processes such as multi-fire hot rolling, double sheet stacking, and steel plate cladding rolling, the sheet is rolled with small variables and multiple passes, which significantly weakens the anisotropy of the sheet, obtains uniform grains, improved microstructure, and improved macroscopic mechanical properties. The titanium alloy sheet prepared by the invention method has a grain size of 2.8 to 4.8μm, a yield strength of about 1000MPa, a tensile strength of about 1100MPa, and an elongation of about 12%. The comprehensive performance is low and cannot meet the urgent needs of modern industry for high-performance titanium alloys.

[0005] Patent document CN 115739996 B provides a preparation method of high-strength and high-plasticity TC4 titanium alloy sheet, comprising the following steps: step one: smelting TC4 titanium alloy raw material in a vacuum consumable furnace to obtain a TC4 titanium alloy ingot; step two: forging the ingot into a slab for rolling; step three: reversing the rolling of the obtained slab into a slab with a thickness of 12 to 15 mm; step four: shearing the slab obtained in step three and water quenching; step five: reversing the rolling of the slab to 3.5 to 4.0 mm; step six: steel plate cladding rolling to obtain a 1.0 to 1.5 mm semi-finished plate; step seven: heat treating the semi-finished plate, alkali pickling and shaving; step eight: cold rolling in steps to 0.6 to 0.8 mm; step nine: heat treatment and correction treatment to obtain a finished TC4 titanium alloy sheet with high strength and high plasticity. The titanium alloy plate prepared by the inventive method has a yield strength of about 900 MPa, a tensile strength of about 1100 MPa, and an elongation of about 20%. The alloy has good elongation but low strength.

[0006] The present invention aims to make the product have both high strength and high toughness while reducing the material cost. It adopts a process combining large deformation warm rolling in the metastable phase region and heat treatment. Large deformation warm rolling in the metastable phase region reshapes the internal structure of the material, and heat treatment adjusts the structure. The material structure is ultrafine lamellar structure + nano-precipitation phase, and the strength and toughness of the material are improved at the same time. The present invention intends to provide a preparation method of high-strength and high-toughness ultrafine-grained titanium alloy material, so that the material has high strength and high toughness. Summary of the invention

[0007] The purpose of the present invention is to provide a method for preparing a high-strength and high-toughness ultrafine-grained titanium alloy material in order to overcome the defects of the above-mentioned prior art. The method has simple process, high production efficiency and excellent material properties.

[0008] The purpose of the present invention can be achieved by the following technical solutions:

[0009] A high-strength and tough ultrafine-grained titanium alloy material, the chemical composition of which is as follows: Al 3.0-6.0%, V 1.0-2.5%, Fe 0.5-2.0%, B 0.01-0.25%, C 0.05-0.15%, N 0.05-0.10%, H≤0.05%, and the rest is Ti and unavoidable impurities.

[0010] Preferably, a high-strength and toughness ultrafine-grained titanium alloy material has the following chemical components in percentage by weight: Al 3.5-5.0%, V 2.0-2.5%, Fe 1.0-2.0%, B 0.01-0.25%, C 0.05-0.12%, N 0.05-0.10%, H≤0.05%, and the rest are Ti and unavoidable impurities.

[0011] Furthermore, a high-strength and toughness ultrafine-grained titanium alloy material also includes 0.01-0.02% Zr, 0.01-0.02% Y and 0.01-0.1% Si.

[0012] A method for preparing a high-strength and high-toughness ultrafine-grained titanium alloy material comprises the following steps:

[0013] Step 1 Vacuum induction melting + electron beam cooling bed melting

[0014] The materials are mixed according to the required alloy composition, smelted into blocks in a vacuum induction furnace, and then smelted in an electron beam cold bed. After melting and refining, the ingots are pulled in a crystallizer to obtain plates.

[0015] Step 2: Homogenization

[0016] The prepared raw material slab is heated and kept warm in the furnace for 2.0 to 6.0 hours.

[0017] Step 3: Hot rolling + large deformation warm rolling

[0018] The homogenized material is subjected to continuous hot rolling and large deformation warm rolling.

[0019] Step 4: Microstructure refinement heat treatment

[0020] The material after large deformation warm rolling is subjected to heat treatment for microstructure refinement.

[0021] Furthermore, a method for preparing a high-strength and high-toughness ultrafine-grained titanium alloy material comprises the following steps:

[0022] Step 2: Homogenization

[0023] The prepared raw material slab is heated to 1020-1050° C. in a furnace, and the heat preservation time is 2.0-6.0 hours.

[0024] Step 3: Hot rolling + large deformation warm rolling

[0025] The homogenized slab is reheated to 900-1000°C and kept warm for 30 minutes.

[0026] Step 4: Microstructure refinement heat treatment

[0027] The plate in step 3 is subjected to a microstructure refinement heat treatment, using a method of continuous high-temperature short-time cycle heat treatment + medium-low temperature tempering.

[0028] Furthermore, the method for preparing the high-strength and high-toughness ultrafine-grained titanium alloy material comprises the following steps:

[0029] In step 2, a stepwise gradient heating method is used, and T r ~(T β-200)℃, the heating rate is 180~240℃ / h,

[0030] (T β -200)℃ and the heating rate is 60~80℃ / h, where T r is room temperature, T β is the phase transition temperature of β phase.

[0031] The large deformation warm rolling in step 3 has a total deformation amount of not less than 85%.

[0032] In step 4, the high temperature short-time insulation temperature is 900-1050°C, the insulation time is 2-10 minutes, the number of cycles is 1-2 times, and the medium and low temperature tempering temperature is 200-500°C.

[0033] The process combines large deformation warm rolling in the metastable phase zone with heat treatment. Large deformation warm rolling in the metastable phase zone reshapes the internal structure of the material, and heat treatment adjusts the organizational structure. The material organization is ultra-fine lamellar organization + nano-precipitation phase, while improving the strength and toughness of the material.

[0034] Furthermore, in the method for preparing a high-strength and toughness ultrafine-grained titanium alloy material, the large deformation rolling process in step 3 is large deformation warm rolling, the large deformation warm forging process is large deformation warm forging, the warm processing range is 500-850°C, and the total deformation is not less than 90%.

[0035] Furthermore, the method for preparing a high-strength and toughness ultrafine-grained titanium alloy material is described. In the material prepared by this method, both the α phase and the β phase are fine equiaxed crystals, and have an obvious lamellar hierarchical structure. The average grain size is less than 10 μm. When the deformation reaches 90%, the average grain size is less than 5.0 μm. When the deformation reaches 95%, the average grain size is less than 1.0 μm.

[0036] Furthermore, in the method for preparing a high-strength and toughness ultrafine-grained titanium alloy material, the yield strength of the alloy is not less than 1200 MPa, the tensile strength is 1400 MPa, and the total elongation is not less than 8%.

[0037] Compared with the prior art, the present invention has the following advantages:

[0038] 1. By optimizing the chemical composition and adopting a specific preparation process, the high-strength and toughness ultrafine-grained titanium alloy material prepared by the present invention has excellent comprehensive properties, with a yield strength of not less than 1200MPa, a tensile strength of 1400MPa, and a total elongation of not less than 8%, which is significantly better than the existing technology.

[0039] 2. The present invention adopts the steps of vacuum induction melting + electron beam cold hearth furnace melting, homogenization treatment, hot rolling blanking + large deformation warm rolling and microstructure refinement heat treatment, etc. The process is relatively simple, and can achieve efficient production, reducing the preparation cost.

[0040] 3. Through the process of combining large deformation warm rolling in the metastable phase zone with heat treatment, the present invention successfully achieves ultra-fine material organization, forming a unique structure of ultra-fine lamellar organization + nano-precipitation phase, while improving the strength and toughness of the material, providing a new way to regulate the performance of titanium alloy materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 The process flow chart of the preparation method of the present invention is shown;

[0042] Figure 2 The process flow chart of Example 1 is shown;

[0043] Figure 3 A grain size photograph of Example 1 is shown;

[0044] Figure 4 The process flow chart of Example 2 is shown;

[0045] Figure 5 A photograph of the grain size of Example 2 is shown. DETAILED DESCRIPTION

[0046] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments. It should be noted that, for those skilled in the art, several changes and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

[0047] Example 1

[0048] A high-strength and tough ultrafine-grained titanium alloy material, characterized in that the weight percentage of its chemical components is: Al 4.5%, V 1.8%, Fe 1.2%, B 0.15%, Nb 0.05%, C 0.1%, N 0.07%, H 0.03%, Zr 0.015%, Y 0.012%, Si 0.05%, and the rest is Ti and unavoidable impurities.

[0049] Al is an α-phase stabilizing element in titanium alloys. It strengthens the α-phase by solid solution and improves the room temperature strength of the alloy. V is a β-phase stabilizing element in titanium alloys. It not only improves the strength of the alloy, but also improves its plasticity, so that the titanium alloy can still maintain good performance when subjected to high stress and complex deformation. The inventors found that when the Al content is controlled at 3.0-6.0% and the V content is controlled at 1.0-2.5%, the uniformity of the α-phase and β-phase of the titanium alloy is the best, and the prepared material performance is also the highest.

[0050] The B element mainly plays the role of heterogeneous nucleation and grain refinement. Generally, the B element is added to the titanium alloy in the form of the intermediate alloy Al-3B. When the B content is less than 0.06%, the grain size decreases with the increase of the B content. When the B content is greater than 0.06%, the B compound particles begin to be distributed in needle shape along the grain boundary, deteriorating the material performance. However, the inventors found that the use of B and Y composite modification can inhibit the tendency of B compounds to aggregate along the grain boundary. If B is continued to be added, the grain size continues to decrease until the B content increases to 0.25%, and the mechanical properties of the material begin to deteriorate.

[0051] The addition of Fe element can improve the strength and toughness of titanium alloy. Its main mechanism of action is to adjust the phase ratio of α and β phases, adjust the morphology of α phase, and increase the lattice distortion of Ti alloy. In addition, the addition of Fe element can reduce the alloy cost.

[0052] The inventors found that adding a certain proportion of Zr and Si to the alloy can move the CCT to the right, providing operation time for the alloy to undergo large deformation warm rolling in the metastable phase region. Large deformation rolling in the metastable phase region can effectively regulate the phase change process inside the material. Through mechanisms such as rolling-induced precipitation and phase transformation strengthening, a small and evenly distributed strengthening phase can be generated, thereby improving the overall performance of the material. During large deformation rolling, defect structures such as high-density dislocations and twins will be generated inside the material. These defect structures will interact with the precipitated phase, matrix, etc., forming a variety of strengthening mechanisms (such as dislocation strengthening, precipitation strengthening, fine grain strengthening, etc.), which together improve the comprehensive performance of the material.

[0053] A method for preparing a high-strength and tough ultrafine-grained titanium alloy material, characterized by comprising the following steps:

[0054] Step 1 Vacuum induction melting + electron beam cooling bed melting

[0055] The materials are divided according to the required alloy composition, melted into blocks in a vacuum induction furnace, and then melted in an electron beam cold bed. After melting and refining, the ingots are pulled in a crystallizer to obtain plates.

[0056] Step 2: Homogenization

[0057] The prepared raw material slab is heated to 1050° C. in a furnace and the heat preservation time is 2.0 hours.

[0058] Step 3: Hot rolling + large deformation warm rolling

[0059] The plate material treated with heating and heat preservation is hot rolled to open the blank, the opening temperature is controlled at 900℃, and the large deformation warm rolling opening temperature is controlled at 850℃.

[0060] Step 4: Microstructure refinement heat treatment

[0061] The plate in step 3 is subjected to microstructure refinement heat treatment by two consecutive high-temperature short-time cycle heat treatments: 900°C for 10 minutes and water cooling, 1000°C for 5 minutes and water cooling, for a total of two cycles, and tempering at 500°C for 2.0 hours.

[0062] The prepared high-strength and tough ultrafine-grained titanium alloy material has a yield strength of 1250MPa, a tensile strength of 1450MPa, and a total elongation of 8.5%.

[0063] Embodiments 2 to 12

[0064] The material alloy composition table in the specific embodiments is shown in Table 1, which is the alloy composition table of the titanium alloy materials of Examples 1 to 12.

[0065]

[0066] Table 1

[0067] The following is Table 2, which lists the specific process and performance parameters in detail. Table 2 shows the specific process and performance of the titanium alloy materials of Examples 1 to 12.

[0068]

[0069] Table 2

[0070] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A high-strength and ultra-fine-grained titanium alloy material, characterized in that: The weight percentage of its chemical composition is: Al3.0-6.0%, V 1.0-2.5%, Fe 0.5-2.0%, B 0.01-0.25%, C 0.05-0.15%, N 0.05-0.10%, H≤0.05%, the rest is Ti and unavoidable impurities.

2. The high-strength and toughness ultrafine-grained titanium alloy material according to claim 1, characterized in that: The weight percentage of its chemical composition is: Al 3.5-5.0%, V 2.0-2.5%, Fe 1.0-2.0%, B 0.01-0.25%, C 0.05-0.12%, N 0.05~0.10%, H≤0.05%, and the rest are Ti and unavoidable impurities.

3. The high-strength and toughness ultrafine-grained titanium alloy material according to claim 1, characterized in that: The chemical composition of the high-strength and toughness ultrafine-grained titanium alloy material also includes: Zr 0.01-0.02%, Y 0.01-0.02% and Si 0.01-0.1%.

4. The method for preparing a high-strength and tough ultrafine-grained titanium alloy material according to claim 1, characterized in that: The steps include: Step 1 Vacuum induction melting + electron beam cooling bed melting The materials are prepared according to the weight percentage of the components of the high-strength and toughness ultrafine-grained titanium alloy material, the materials are smelted into blocks in a vacuum induction furnace, and then electron beam cold bed smelting is performed, and after melting and refining, ingots are pulled in a crystallizer to obtain sheet materials; Step 2: Homogenization The prepared raw material slab is heated and kept warm for 2.0 to 6.0 hours in the furnace; Step 3: Hot rolling + large deformation warm rolling The homogenized material is subjected to continuous hot rolling and large deformation warm rolling; Step 4: Microstructure refinement heat treatment The material after large deformation warm rolling is subjected to heat treatment for microstructure refinement.

5. The method for preparing a high-strength and tough ultrafine-grained titanium alloy material according to claim 4, characterized in that: The steps include: Step 2: Homogenization The prepared raw material slab is heated to 1020-1050°C in the furnace, and the heat preservation time is 2.0-6.0 hours; Step 3: hot rolling + large deformation warm rolling Reheat the homogenized slab to 900-1000°C and keep it warm for 30 minutes; Step 4: Microstructure Refining Heat Treatment The plate obtained in step 3 is subjected to a microstructure refinement heat treatment by a method of continuous high-temperature short-time cycle heat treatment + medium-low temperature tempering.

6. The method for preparing a high-strength and tough ultrafine-grained titanium alloy material according to claim 4, characterized in that: The steps include: In step 2, a stepwise gradient heating method is used, and T r ~(T β The heating rate from (T -200)℃ is 180~240℃ / h, (T β -200)℃ and the heating rate is 60~80℃ / h, where T r is room temperature, T β is the phase transition temperature of β phase; The large deformation warm rolling in step 3 has a total deformation of not less than 85%; In step 4, the high temperature short-time insulation temperature is 900-1050°C, the insulation time is 2-10 minutes, the number of cycles is 1-2 times, and the medium and low temperature tempering temperature is 200-500°C.

7. The method for preparing a high-strength and tough ultrafine-grained titanium alloy material according to claim 4, characterized in that: The large deformation warm rolling in step 3 has a warm processing range of 500-850° C. and a total deformation amount of not less than 90%.

8. The method for preparing a high-strength and tough ultrafine-grained titanium alloy material according to claim 4, characterized in that: The α phase and β phase in the material prepared by this method are both fine equiaxed crystals with a distinct lamellar hierarchical structure. The average grain size is less than 10 μm. When the deformation reaches 90%, the average grain size is less than 5.0 μm. When the deformation reaches 95%, the average grain size is less than 1.0 μm.

9. A high-strength and tough ultrafine-grained titanium alloy material and a preparation method thereof according to claims 1 and 5, characterized in that: The yield strength of the alloy is not less than 1200MPa, the tensile strength is 1400MPa, and the total elongation is not less than 8%.

Citation Information

Cited By

  • Niobium-yttrium-containing titanium alloy plate, preparation method and battery shell

    CN122012990A

  • Nb-Y-Ti alloy plate, preparation method and battery shell

    CN122012990B